Relationship Between Employment Conflict with Discipline Of Employees: Hubungan Antara Konflik Kerja dengan Kedisiplinan pada Karyawan - Sunaryo; Ghozali Rusyid Affandi (Universitas Muhammadiyah Sidoarjo, 2022)
This study explores the relationship between work conflict and employee discipline within an organization, aiming to uncover potential implications for achieving organizational goals. Utilizing quantitative methods, a survey scale was administered to 254 randomly selected employees from a population of 705 in PT X Tbk. Surabaya. The analysis revealed a significant negative correlation (r = -0.263**, p < 0.005) between work conflict and employee discipline. These findings indicate that work conflict acts as a detrimental factor influencing the discipline of employees. The implications suggest that addressing work conflict is crucial for fostering a disciplined work environment, ultimately contributing to organizational success. Highlights: Work conflict negatively affects employee discipline: The study demonstrates a significant negative correlation between work conflict and employee discipline, emphasizing the detrimental impact of work conflict on maintaining a disciplined workforce. Quantitative methods for measuring work conflict and employee discipline: The research employed quantitative methods, specifically a survey scale, to collect and analyze data, providing a structured and objective approach to investigate the relationship between work conflict and employee discipline. Implications for organizational success: The findings highlight the importance of addressing work conflict to foster a disciplined work environment. By mitigating work conflict, organizations can enhance employee discipline, thereby increasing their chances of achieving desired organizational goals. Keywords: work conflict, employee discipline, organizational goals, quantitative methods, PT X Tbk.